A Tonoplast-Associated Calcium-Signaling Module Dampens ABA Signaling during Stomatal Movement. Issue 4 (13th June 2018) - Song, Shi-Jian; Feng, Qiang-Nan; Li, Chun-Long; Li, En; Liu, Qi; Kang, Hui; Zhang, Wei; Zhang, Yan; Li, Sha
Abstract : Arabidopsis PAT10 and its downstream tonoplast calcineurin B-like proteins (CBLs) and CBL-interacting protein kinases negatively mediate ABA signaling in guard cells by promoting vacuolar potassium influx and preventing fast vacuolar convolution. Abstract: Stomatal movement, critical for photobiosynthesis, respiration, and stress responses, is regulated by many factors, among which abscisic acid (ABA) is critical. Early events of ABA signaling involve Ca 2+ influx and an increase of cytoplasmic calcium ([Ca 2+ ]cyt ). Positive regulators of this process have been extensively studied, whereas negative regulators are obscure. ABA-induced stomatal closure involves K + flux and vacuolar convolution. How these processes are connected with Ca 2+ is not fully understood. We report that pat10-1, a null mutant of Arabidopsis ( Arabidopsis thaliana ) PROTEIN S-ACYL TRANSFERASE10 ( PAT10 ), is hypersensitive to ABA-induced stomatal closure and vacuolar convolution. A similar phenotype was observed in cbl2;cbl3, the double mutant of CBL2 and CBL3, whose tonoplast association depends on PAT10. Functional loss of the PAT10-CBL2/CBL3 system resulted in enhanced Ca 2+ influx and [Ca 2+ ]cyt elevation. Promoting vacuolar K + accumulation by overexpressing NHX2 suppressed ABA-hypersensitive stomatal closure and vacuolar convolution of the mutants, suggesting that PAT10-CBL2/CBL3 positively mediates vacuolar K + accumulation. We have identified CBL-interacting protein kinases (CIPKs) that mediate CBL2/CBL3 signaling during ABA-induced stomatal movement. Functional loss of the PAT10-CBL2/3-CIPK9/17 system in guard cells enhanced drought tolerance. We propose that the tonoplast CBL-CIPK complexes form a signaling module that negatively regulates ABA signaling during stomatal movement.